Challenges and future direction of molecular research in air pollution-related lung cancers. (April 2018) - Shahadin, Maizatul Syafinaz; Ab. Mutalib, Nurul Syakima; Latif, Mohd Talib; Greene, Catherine M.; Hassan, Tidi
Highlights: Air pollution was classified as Group 1 carcinogen in human by IARC, however the molecular mechanism of carcinogenesis was limited. Epidemiological studies showed positive association between different composition of air pollution and lung cancer including non-smoker. Molecular studies on air-pollution related lung cancer are limited due to several complex challenges in research field. Abstract: Hazardous air pollutants or chemical release into the environment by a variety of natural and/or anthropogenic activities may give adverse effects to human health. Air pollutants such as sulphur dioxide (SO2), nitrogen oxides (NOx), carbon monoxide (CO), heavy metals and particulate matter (PM) affect number of different human organs, especially the respiratory system. The International Agency for Research on Cancer (IARC) reported that ambient air pollution is a cause of lung cancer. Recently, the agency has classified outdoor air pollution as well as PM air pollution as Group 1 carcinogens. In addition, several epidemiological studies have shown a positive association between air pollutants to lung cancer risks and mortality. However, there are only a few studies examining the molecular effects of air pollution exposure specifically in lung cancer due to multiple challenges to mimic air pollution exposure in basic experimentation. Another major issue is the lack of adequate adjustments for exposure misclassification as air pollution may differ temporo-spatially and socioeconomically. Thus, the purpose of this paper is to review the current molecular understanding of air pollution-related lung cancer and potential future direction in this challenging yet important research field.